If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 810(pi) = 324(pi) + (pi) * 18h Reorder the terms for easier multiplication: 810ip = 324ip + 18ip * h Multiply ip * h 810ip = 324ip + 18hip Reorder the terms: 810ip = 18hip + 324ip Solving 810ip = 18hip + 324ip Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-18hip' to each side of the equation. -18hip + 810ip = 18hip + -18hip + 324ip Combine like terms: 18hip + -18hip = 0 -18hip + 810ip = 0 + 324ip -18hip + 810ip = 324ip Add '-324ip' to each side of the equation. -18hip + 810ip + -324ip = 324ip + -324ip Combine like terms: 810ip + -324ip = 486ip -18hip + 486ip = 324ip + -324ip Combine like terms: 324ip + -324ip = 0 -18hip + 486ip = 0 Factor out the Greatest Common Factor (GCF), '18ip'. 18ip(-1h + 27) = 0 Ignore the factor 18.Subproblem 1
Set the factor 'ip' equal to zero and attempt to solve: Simplifying ip = 0 Solving ip = 0 Move all terms containing i to the left, all other terms to the right. Simplifying ip = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1h + 27)' equal to zero and attempt to solve: Simplifying -1h + 27 = 0 Reorder the terms: 27 + -1h = 0 Solving 27 + -1h = 0 Move all terms containing i to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -1h = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -1h = 0 + -27 -1h = 0 + -27 Combine like terms: 0 + -27 = -27 -1h = -27 Add 'h' to each side of the equation. -1h + h = -27 + h Combine like terms: -1h + h = 0 0 = -27 + h Simplifying 0 = -27 + h The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2x+25=145 | | 12x+(12-2)=12+11x | | 8x+11=51 | | 6x+8=74 | | 8x+15=63 | | c(c+5)=0 | | u^2-2u-24=0 | | 186-2x=34x+22 | | 6x+9=3x-21 | | .20x+60=.40(x+120) | | 5=9-7x | | 3x+2(3)=91.50 | | -3*0+7= | | 14-8x=47-29x | | 5*0+7= | | 20-x-4x=10 | | 3.2d+1.5d=42.3 | | 4x+16=68 | | 30x+24=-45x-6 | | p^2-8p+15=0 | | (-12y)-2y= | | 7-(-18)= | | 5.7(x-4)=-0.3x+19.2 | | 3x+10x=5x | | 8x^2+26x+15=0 | | 15.25=2.5d+1.5 | | x-4y-2=0 | | 6x-4=4x+2 | | 9ln(x-8)-8lnx= | | -2-(-5)= | | 3x-5=9x+8 | | 6(3x-1)=3(6x+5) |